RISCOS ERGONÔMICOS NA EXPLORAÇÃO DE MADEIRA EM UNIDADE DE PRODUÇÃO ANUAL NA AMAZÔNIA MERIDIONAL - SILVA, IVAN CLEITON DE OLIVEIRA (2023)
Sustainable forest management in the Amazon must be executed under environmental, legal, and safety guidelines and the health of workers is of great importance for the country and society, since the workers in this region are subjected to various unknown ergonomic risks that implicate quality of life. In this context, the goal was to execute a diagnostic of the ergonomic risks to which the workers are exposed in wood exploration in the managed forest, subsidizing the implementation of ergonomic solutions for the safety and health of the workers. The work was executed in a tropical forest under conventional management of the northern region of Mato Grosso state. Wood cutting and lugging operations of varying densities were studied. Evaluations of the levels of exposure to heat, sound and vibration during work tasks were executed, as well as of body postures and physical workload, using specific equipment and methodologies. Discriminating analyses were executed for the grouping of ergonomic variables and the correlation with wood density. WBT limits indicated the workers’ exposure to thermal overload. During the lugging operation, the machine showed levels of vibration superior to the level of action, while during the cutting, the levels of vibration were above the exposure limit (> 5 m/s²), most notably in higher density wood with vibrations at 13.96 m/s². The level of noise was superior to the limit of exposure in all densities and was kept within the acceptable limit in lumber lugging. The tree cutting and lugging activities did not provide an elevated physical workload, nor potential postural risks that would demand immediate action in changing the work routine. The discriminating analysis indicated the correlation between density, cardiovascular load, and hand-arm vibrations in the cutting operation, and the correlation between density, full-body vibration and noise in the lugging operations, indicating a high correlation of wood density with the ergonomic variables. Wood density is an operational variable of great influence in levels of occupational vibration in the analyzed operations, demanding the implementation of mitigating ergonomic measures for the preservation of workers’ health in the Amazon region.